1995
DOI: 10.1089/jir.1995.15.115
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Acute Experimental Autoimmune Encephalomyelitis in the Lewis Rat by Oral Administration of Type 1 Interferons

Abstract: The effect of orally administered type 1 interferons on the severity of acute experimental autoimmune encephalomyelitis (EAE), a T cell-mediated autoimmune disease, was examined by inoculation of Lewis rats with guinea pig myelin basic protein (GPMBP) and complete Freund's adjuvant. Rats were fed either rat species-specific or human recombinant type 1 interferon (IFN) or mock IFN daily for 7 days preceding immunization and for 21 days thereafter. There was a significant decrease in the clinical score and infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…Both oral and intraperitoneal administration of IFN can decrease peripheral white blood cell counts, although circulating antibody to IFN can block this effect only with intraperitoneal administration but not with oral administration [16]. Moreover, it has been shown that low-dose IFN, while ineffective if given parenterally, is able to suppress disease in the EAE model when given orally [9]. Such potential efficacy, combined with the obvious benefit of ease of administration, has made oral IFN therapy a viable alternative to injected therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both oral and intraperitoneal administration of IFN can decrease peripheral white blood cell counts, although circulating antibody to IFN can block this effect only with intraperitoneal administration but not with oral administration [16]. Moreover, it has been shown that low-dose IFN, while ineffective if given parenterally, is able to suppress disease in the EAE model when given orally [9]. Such potential efficacy, combined with the obvious benefit of ease of administration, has made oral IFN therapy a viable alternative to injected therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Rats were treated daily with various doses (10 2 , 10 3 , 10 4 or 10 5 IU) of mouse recombinant IFN-β starting 7 days before immunization through the day of killing. This protocol was similar to that previously described for EAE [9]. Because IFN is absorbed best from the oropharyngeal cavity [26], the IFN-β was administered by direct application to the oropharyngeal mucosa using a micropipette.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These problems are, in part, due to the lack of diversity in EAE models using inbred strains of mice, various misconceptions about our understanding of the pathophysiology of EAE from knockout mice, the relatively small numbers of animals used in EAE test systems, and the short time interval for testing even 'chronic' therapies in EAE, in which experiments might need to run for years, not weeks or months, to model chronic human therapy. Despite its pitfalls, EAE has been a useful model for predicting success with clinical trials in multiple sclerosis (MS).Currently, there are several approved therapies for MS, including glatiramer acetate [1-8], mitoxantrone [9-11], various b interferons (IFNs) [12,13] and natalizumab [14][15][16][17], which has been withdrawn currently from the market by its manufacturers. Glatiramer acetate is one of the hallmarks of current therapy and was developed based on its ability to modulate EAE [1][2][3][4][5][6][7][8].…”
mentioning
confidence: 99%
“…Currently, there are several approved therapies for MS, including glatiramer acetate [1][2][3][4][5][6][7][8], mitoxantrone [9][10][11], various b interferons (IFNs) [12,13] and natalizumab [14][15][16][17], which has been withdrawn currently from the market by its manufacturers. Glatiramer acetate is one of the hallmarks of current therapy and was developed based on its ability to modulate EAE [1][2][3][4][5][6][7][8].…”
mentioning
confidence: 99%